Effect of Management Ownership, Industry Auditor Specialization, Audit Complexity and Auditor Switching on Timeliness of Financial Reporting - Dedik Nur Triyanto; Ajeng Luthfiyatul Farida; Namira Permata (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
This study aims to determine the effect of managerial ownership, auditor industry specialization, complexity audit, and auditor switching on the timeliness of submitting financial reports to Energy sector companies listed on the Indonesia Stock Exchange in 2017-2021. The method in this research is a quantitative research method. The population in this study are energy sector companies listed on the Indonesia Stock Exchange during 2017-2020. The sampling technique in this study used a purposive sampling technique with 41 research samples within five years so that a total of 205 research data were obtained. Data analysis used descriptive statistical analysis method and logistic regression analysis using SPSS 26 software. The results showed that managerial ownership, auditor industry specialization, audit complexity had a positive effect on the timeliness of financial reporting, while switching auditors did not affect on the timeliness of financial reporting. The accuracy of submitting financial statements to companies tends to be influenced by factors such as high levels of managerial ownership, auditor industry specialization, and audit complexity, but the presence of switching auditors in the company does not affect the time of submission of financial statements.